Start here : a road map to reducing mass incarceration - Berman, Greg; Adler, Julian (The New Press, 2018)
A bold agenda for criminal justice reform based on equal parts pragmatism and idealism, from the visionary director of the Center for Court Innovation, a leader of the reform movement. Everyone knows that the United States leads the world in incarceration, and that our political process is gridlocked. What can be done right now to reduce the number of people sent to jail and prison? This essential book offers a concrete roadmap for both professionals and general readers who want to move from analysis to action. In this forward-looking, next-generation criminal justice reform book, Greg Berman and Julian Adler of the Center for Court Innovation highlight the key lessons from these programs-engaging the public in preventing crime, treating all defendants with dignity and respect, and linking people to effective community-based interventions rather than locking them up. Along the way, they tell a series of gripping stories, highlighting gang members who have gotten their lives back on track, judges who are transforming their courtrooms, and reformers around the country who are rethinking what justice looks like. While Start Here offers no silver bullets, it does put forth a suite of proven reforms-from alternatives to bail to diversion programs for mentally ill defendants-that will improve the lives of thousands of people right now. Start Here is a must-read for everyone who wants to start dismantling mass incarceration without waiting for a revolution or permission. Proceeds from the book will support the Center for Court Innovation's reform efforts.